Conditional inactivation of Npy1r gene in mice induces behavioural inflexibility and orbitofrontal cortex hyperactivity that are reversed by escitalopram. (1st May 2018) - Longo, Angela; Fadda, Melissa; Brasso, Claudio; Mele, Paolo; Palanza, Paola; Nanavaty, Ishira; Bertocchi, Ilaria; Oberto, Alessandra; Eva, Carola
Abstract: Cognitive flexibility is the ability to rapidly adapt established patterns of behaviour in the face of changing circumstance and depends critically on the orbitofrontal cortex (OFC). Impaired flexibility also results from altered serotonin transmission in the OFC. The Y1 (Y1R) and Y5 (Y5R) receptors for neuropeptide Y (NPY) colocalize in several brain regions and have overlapping functions in regulating cognition and emotional behaviour. The targeted disruption of gene encoding Y1R ( Npy1r gene) in Y5R containing neurons (Npy1r Y5R −/− mice) increases anxiety-like behaviour and spatial reference memory. Here we used the same conditional system to analyse whether the coordinated expression of the Y1R and Y5R might be required for behavioural flexibility in reversal learning tasks, OFC serotoninergic tone and OFC neural activity, as detected by immunohistochemical quantification of the immediate-early gene, c -Fos. In addition, we investigated whether the acute treatment of Npy1r Y5R −/− mice with the selective serotonin reuptake inhibitor escitalopram affected behavioural flexibility and OFC c -Fos expression. Npy1r Y5R −/− male mice exhibit an impairment in performing the reversal task of the Morris water maze and the water T-maze but normal spatial learning, working memory and sociability, compared to their control siblings. Furthermore, Npy1r Y5R −/− male mice display decreased 5-hydroxytriptamine (5-HT) positive fibres and increased baseline neural activity in OFC. Importantly, escitalopram normalizes OFC neural activity and restores behavioural flexibility of Npy1r Y5R −/− male mice. These findings suggest that the inactivation of Y1R in Y5R containing neurons increases pyramidal neuron activity and dysregulates serotoninergic tone in OFC, whereby contributing to reversal learning impairment. Highlights: Reversal learning, a form of behavioural flexibility, depends on OFC functional integrity. Deletion of Npy1r gene in Y5R neurons increases inflexibility and OFC neuronal activity. Deletion of Npy1r gene in Y5R neurons decreases 5-HT fibers in OFC. SSRI treatment rescues reversal learning impairment and OFC hyperactivity of Npy1r Y5R −/− mice. NPY-Y1R transmission in OFC plays a role in behavioural flexibility that is impaired in OCD.